Balancing Biodiversity with Land Use in the Lowland Rainforests of Peninsular Malaysia, a Discussion Paper - Ibrahim, Ab. Latif (National Institute for Environmental Studies, Japan, 2006)
The extinction risk among the terrestrial vertebrates of Southeast Asia, including Indo-Burma and archipelagic regions such as Philippines, Sundaland and Wallacea is among the highest in the world. The basis for this elevated risk in recent times is largely due to the clearing of forest habitat and subsequent conversion to plantations or human settlements where a significant fraction of vertebrate species are endemic. Among a total of 500 terrestrial species of birds (including inland species that occupy riparian habitats) found in Peninsular Malaysia, 156 are endemic to the Sundaland (Peninsular Malaysia, Sumatra, Java, Bali, Borneo and smaller island west of the Wallace Line) of which 82 (53%) are now red-listed by IUCN. Lowland forests, primarily the dipterocarp rainforests (as represented by the Pasoh Reserve Forest) have undergone the most extensive shrinkage of their former area; hence they carry the highest risk of extinction of biota. Continued expropriation of timber and conversion to plantation agroforestry will further fragment these forests and reduce the likelihood that fully functioning ecosystems can regenerate. We discuss a strategy to identify what remains of primary lowland forests in Peninsular Malaysia, especially patches of forest with adequate area to support viable populations of species as a functional community and to overcome the likelihood of loss through stochastic events. Stimulation of a competitive industry with the oil palm industry that maintains intact natural forest would bolster the security of the rainforest from an economic perspective.